Proceedings of the 2015 (6th) International Conference on Engineering, Project, and Production Management 2015
DOI: 10.32738/ceppm.201509.0004
|View full text |Cite
|
Sign up to set email alerts
|

Formwork and False Work Hazards in Construction: Status and Effects in Bloemfontein, South Africa

Abstract: Despite efforts to enhance health and safety (H&S) practices, construction workers' practices in relation to formwork and false work usage has been noted as a leading source of injuries and accidents in South Africa. This paper reports on an exploratory research that is aimed at reducing formwork and false work hazards occurrence on construction sites in South Africa. The study obtains primary data from construction participants in Bloemfontein, South Africa. The data were obtained by interviewing management o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Possible failures of formwork can be caused by mistakes during erection, wrong calculations of weight acting on the formwork, extra loads, or natural disasters [3]. Several worker interviews were conducted in order to establish the most common hazards on construction sites caused by falsework [4]. They have concluded that the main cause of formwork and falsework accidents on sides is due to the lack of planning, stripping of formwork, falling objects, floor collapse, and mishandling of material.…”
Section: Introductionmentioning
confidence: 99%
“…Possible failures of formwork can be caused by mistakes during erection, wrong calculations of weight acting on the formwork, extra loads, or natural disasters [3]. Several worker interviews were conducted in order to establish the most common hazards on construction sites caused by falsework [4]. They have concluded that the main cause of formwork and falsework accidents on sides is due to the lack of planning, stripping of formwork, falling objects, floor collapse, and mishandling of material.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, formwork failure can occur during concrete pours and can cause leakage of concrete, leading to possible complete structural collapse, injuries, and fatalities. Based on several interviews from construction workers, it was concluded that the most common formwork and falsework failures are because of lack of planning, falling objects, stripping of formwork, mishandling of material, and floor collapse ( 2 ).…”
mentioning
confidence: 99%